Evaluation of in vitro antidiabetic and antioxidant activity of leaf extracts of Ecbolium linneanum kurz.: GC-MS and HR-LCMS based metabolite profiling and an in silico approach - Srilakshmi Nallapaty, Narender Malothu, Sathish Kumar Konidala, Anka Rao Areti (Journal of Applied Pharmaceutical Science, 2024)
The Ecbolium linneanum Kurz., plant has been used historically in traditional medicine to treat a wide range of ailments including gout, rheumatism, etc. Therefore, we set out to investigate its anti-diabetic and antioxidant effects. This study was executed by assessing its in vitro antidiabetic and antioxidant effects and characterizing the phytochemical composition of the plant material. The antidiabetic action was measured using the α-amylase assay, while antioxidant activity was evaluated using the 2,2-Diphenyl-1-picrylhydrazyl) (DPPH), ferric ion reducing antioxidant power, and hydrogen peroxide assays. The compounds were also put to in-silico tests for drug-likeness, absorption, distribution, metabolism, and excretion profile, and binding interactions with α-amylase. In this study, the methanolic leaf extract significantly inhibited α-amylase activity (IC50 – 684.94 g/ml). An impressive level of antioxidant activity (87.78% radical scavenging) was measured with the DPPH test. About 57 phytochemicals were discovered in the methanolic leaf extract employing gas chromatography-mass spectroscopy and high-resolution liquid chromatography-mass spectrometry analyses. About 28 compounds were found promising in oral bioavailability and drug-likeness properties in in-silico research. A few compounds like rhodotoxin A, pyrophosphite a, and 23-acetoxysoladulcidine demonstrated a high-binding affinity for α-amylase. The findings of this study provide preliminary evidence that leaf extracts of E. linneanum may possess anti-diabetic and antioxidant activities. This plant is an excellent source to instigate in researching new natural candidates for antidiabetic therapy.
Keywords: Antidiabetic activity, antioxidant activity, DPPH assay, GC-MS analysis, and ADME profile